2021
DOI: 10.1093/eurjpc/zwab215
|View full text |Cite
|
Sign up to set email alerts
|

Big gamma-glutamyltransferase is associated with epicardial fat volume and cardiovascular outcome in the general population

Abstract: Aims Gamma-glutamyltransferase (GGT) has been recognized as a cardiovascular risk factor, and its highest molecular weight fraction [big GGT (b-GGT)] is found in vulnerable atherosclerotic plaques. We explored the relationship between b-GGT, computed tomography findings, and long-term outcomes in the general population. Methods and results Between May 2010 and October 2011, subjects aged 45–75 years living in a Tuscan city an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…More recently, Aimo et al reported that big GGT, the highest‐molecular‐weight fraction of GGT, was associated with a composite of cardiovascular death or acute coronary syndrome requiring urgent coronary revascularization and epicardial fat volume, all of which is related to plaque inflammation. 18 In the present study, there was a significant positive linear trend between GGT and CRP, a marker of inflammation ( r =0.16; P <0.001). Our results support previous findings that GGT activity is a surrogate of systemic inflammation.…”
Section: Discussionsupporting
confidence: 58%
“…More recently, Aimo et al reported that big GGT, the highest‐molecular‐weight fraction of GGT, was associated with a composite of cardiovascular death or acute coronary syndrome requiring urgent coronary revascularization and epicardial fat volume, all of which is related to plaque inflammation. 18 In the present study, there was a significant positive linear trend between GGT and CRP, a marker of inflammation ( r =0.16; P <0.001). Our results support previous findings that GGT activity is a surrogate of systemic inflammation.…”
Section: Discussionsupporting
confidence: 58%
“…Overall, 29 studies conducted between 2012 and 2022, with a total of 19 709 participants, were included in the meta-analysis. The included studies were conducted in Austria, 30 China, 21,31 Denmark, 32 Germany, 33,34 Italy, 35 Japan, [36][37][38][39][40] Mexico, 41 South Korea, [42][43][44] Taiwan, 45 Turkey, [46][47][48][49][50][51][52] the United Kingdom, 22 and the United States. [53][54][55][56] The mean age of participants was 60 years, with 62.1% being male.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%